Brahms and His World : Revised Edition - Karnes, Kevin, 1972-; Frisch, Walter, 1951- (Book collections on Project MUSE., 2009)
A key collection of essays for listeners, performers, and scholars interested in Brahm's life, work, and times on the occasion of a music festival held at Bard College, August 1990.